Cyber-bullying among adolescent at school: A literature review - Nhung, Le Ngoc Ai; Basuki, Agus; Mahfud, Tuatul; Saputro, Ida Nugroho (International Journal of Psychosocial Rehabilitation, 2020)
Changes in aggressive student behavior in the digital age have modernized a new type of bullying, cyber-bullying. Cyber-bullying has become a new spotlight for scientists because it is a new form of bullying in the digital age. Many studies that have discussed cyber-bullying include the causes of cyber-bullying, the impact of cyber-bullying, and the protective actions of cyber-bullying. However, the research is still discussed separately. This study uses the literature review method to reveal the causes of cyber-bullying, the impact of cyber-bullying, and the protective actions of cyber-bullying in schools. There are 52 articles on Taylor and Francis's online and The National Center for Biotechnology Information. The main findings show that cyber- bullying is caused by family factors, social skills, etc. Cyber-bullying can cause emotional problems such as symptoms of depression and anxiety. Cyber-bullying protective measures include limiting internet access, monitoring student activity, etc. This study has implications for school stakeholders to determine methods of reducing cyber-bullying in schools.